Political Limits to Globalization - Acemoğlu, Daron; Yared, Pierre (American Economic Review, 2010)
We live in an unprecedented age of globalization, where technology, ideas, factors of production, and goods are increasingly mobile across national boundaries. The current wave of globalization is distinguished from previous ones in part because of the major role of infor mation technology. Nevertheless, globalization is not irreversible. Openness to international trade, finance, and technology is a choice that countries make, and despite the facilitating role of information technology, many countries, even many leading players in the world econ omy including the United States, China, India, Brazil, and Russia, could decide to close their borders. A major cause of the end of the previ ous (also historically unprecedented ) nineteenth century wave of globalization was disillusion ment with the international economic order, in